Zif-67@zif-8 / polyacrylonitrile nanofiber membrane, preparation method and application thereof
Patent Information
- Application Number
- CN202611166221.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的在于解决如何将双金属Zn/Co-ZIFS应用于处理工业烟气中空气污染的问题,提供了一种ZIF-67@ZIF-8/PAN纳米纤维膜、制备方法及其应用
[0021]1、本发明合成的ZIF-67@ZIF-8/ PAN纳米纤维膜具有高比表面积,原位生长制作的Co(II)/Zn(II)=3:1时ZIF-67@ZIF-8/PAN纳米纤维膜的比表面积为780~920m2/g,大于常规下ZIF-67@ PAN纳米纤维膜的600~700 m2/g,ZIF-8@PAN纳米纤维膜的650~750 m2/g和共混纺丝的ZIF-67@ZIF-8/PAN纳米纤维膜的680~850 m2/g,表现出优秀的吸附活性,可依靠范德华力捕获气态SO2、NO、NO2小分子,把烟气中酸性气体截留禁锢在孔道内,有效协同吸附硫氧化物和氮氧化物效率分别达到89.4%和78.7%;
Smart Images

Figure CN122875199A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanofiber membrane technology, specifically to a ZIF-67@ZIF-8 / PAN nanofiber membrane, its preparation method, and its application. Background Technology
[0002] With rapid economic development and global industrialization, air pollution has become one of the most serious threats to human health and life. Air pollution primarily consists of two components: fine particulate matter (PM) pollutants and harmful gases; both seriously threaten human health. PM, including PM10 (≤10 μm) or PM2.5 (≤2.5 μm), is considered the most harmful particulate matter based on its aerodynamic diameter because it easily passes through the respiratory tract, leading to chronic respiratory and cardiovascular diseases. Nitrogen dioxide (NO2) and sulfur dioxide (SO2) are identified by the World Health Organization (WHO) as major sources of air pollution, and changes in their concentrations have a significant impact on human health and environmental quality. These harmful substances pose a serious threat to environmental safety and public health, making the control of nitrogen oxide and sulfur oxide emissions one of the most pressing challenges in mitigating industrial pollution. The most effective way to protect humans from air pollution is to use air filtration materials to intercept these particles and harmful gases. Therefore, the ever-growing global demand for clean air has prompted scientists to develop high-performance air filters to synergistically treat particulate pollutants and other harmful gases.
[0003] In practical industrial and environmental applications, adsorption methods offer significant advantages for treating harmful gases due to their high efficiency, operational flexibility, low energy consumption, cost-effectiveness, and adaptability to complex environments. Common adsorbents used for absorbing fine particulate pollutants and harmful gases include activated carbon, amine-modified activated carbon, hydrophobic molecular sieves, metal-organic frameworks (MOFs), and polymer resins. However, different adsorbents have limitations in practical applications. MOFs, due to their superior adsorption capacity, are among the most promising adsorbents for formaldehyde and acetaldehyde. Zeolite pyrazole frameworks (ZIFs) are formed through coordination bonds between metal ions and pyramide ligands, with a structure similar to zeolites, where metal ions and pyrazole units replace silicon and oxygen positions, respectively. Some well-known properties of ZIF materials include tunable structure, porosity, exceptional thermal stability, chemical and mechanical stability, and high surface area. Bimetallic ZnCo-ZIFS is a new representative of the ZIF family, containing two tetrahedral metal centers, Zn(II) and Co(II), randomly arranged within the framework. The combination of zinc and cobalt enhances the physical and chemical properties of ZnCo-ZIFs, resulting in larger pore volumes compared to monometallic ZIFs. However, research on the effects of bimetallic ZnCo-ZIFs on air pollution in industrial flue gas remains scarce and requires further investigation.
[0004] In view of the above-mentioned defects, the inventors of this invention have finally obtained this invention after a long period of research and practice. Summary of the Invention
[0005] The purpose of this invention is to solve the problem of how to apply bimetallic Zn / Co-ZIFS to treat air pollution in industrial flue gas, and to provide a ZIF-67@ZIF-8 / PAN nanofiber membrane, its preparation method and its application.
[0006] To achieve the above objectives, this invention discloses a ZIF-67@ZIF-8 / PAN nanofiber membrane, which is obtained by in-situ growth of ZIF-67 / ZIF-8 nanoparticles on a polyacrylonitrile fiber matrix. When Co(II) / Zn(II) = 3:1, the specific surface area of the ZIF-67@ZIF-8 / PAN nanofiber membrane is 780~920 m². 2 / g, which is greater than the conventional ZIF-67@PAN nanofiber membrane's 600~700 μm. 2 / g, ZIF-8@PAN nanofiber membrane 650~750 μm 2 / g and the 680~850 m of ZIF-67@ZIF-8 / PAN nanofiber membranes spun in blend with PAN 2 / g, exhibiting excellent adsorption activity. The microstructure of the ZIF-67@ZIF-8 / PAN nanofiber membrane consists of smaller rhombic dodecahedral ZIF8 nanoparticles and larger rhombic dodecahedral ZIF67 nanoparticles embedded and embedded on the surface and inside of a PAN fiber matrix formed by randomly interlaced stacked filaments.
[0007] This invention also discloses a method for preparing the above-mentioned ZIF-67@ZIF-8 / PAN nanofiber membrane, comprising the following steps:
[0008] S1, a polyacrylonitrile polymer solution is obtained by dissolving polyacrylonitrile in dimethylformamide and stirring.
[0009] S2, add cobalt nitrate hexahydrate and anhydrous zinc nitrate to the polyacrylonitrile polymer solution obtained in step S1, and stir to obtain PAN / Co(Ac)2 / Zn(NO3)2 solution;
[0010] S3, the PAN / Co(Ac)2 / Zn(NO3)2 solution obtained in step S2 is introduced into a syringe connected to a metal needle, and PAN / Co / Zn nanofiber membrane is obtained after electrospinning.
[0011] S4. The PAN / Co / Zn nanofiber membrane obtained in step S3 is immersed in a 2-methylimidazole / ethanol precursor solution prepared by dissolving 2-methylimidazole in ethanol, and then dried to obtain ZIF-67@ZIF-8 / PAN nanofiber membrane.
[0012] In step S1, the stirring temperature is 40°C, the stirring time is 2 hours, and the concentration of the polyacrylonitrile polymer solution is 6 wt%.
[0013] In step S2, the molar ratio of cobalt nitrate hexahydrate to anhydrous zinc nitrate is 1:1 to 1:5.
[0014] In step S2, the stirring temperature is room temperature (25°C) and the stirring time is 1 hour.
[0015] In step S3, a 15 kV DC high voltage is applied between the tip of the metal needle and the grounded roller, and the roller is covered with silicone paper as a base.
[0016] In step S3, during the electrospinning process, the solution injection rate is set to 0.0012 mm / h, the distance from the tip of the metal needle to the roller is set to 20 cm, and the electrospinning time is set to 1.5 h.
[0017] In step S3, during the electrospinning process, the temperature is controlled at 23 ± 2 ℃ and the relative humidity is controlled at 50 ± 3%.
[0018] In step S4, the PAN / Co / Zn nanofiber membrane is immersed in a 2-methylimidazole / ethanol precursor solution for 3 hours; the drying process is as follows: the membrane is dried in an electric drying oven at 60°C for 10 minutes.
[0019] The present invention also discloses the application of the above-mentioned ZIF-67@ZIF-8 / PAN nanofiber membrane in industrial flue gas denitrification and desulfurization.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] 1. The ZIF-67@ZIF-8 / PAN nanofiber membrane synthesized in this invention has a high specific surface area. The specific surface area of the ZIF-67@ZIF-8 / PAN nanofiber membrane prepared by in-situ growth with Co(II) / Zn(II) = 3:1 is 780~920 m². 2 / g, which is greater than the conventional ZIF-67@PAN nanofiber membrane's 600~700 μm. 2 / g, ZIF-8@PAN nanofiber membrane 650~750 μm 2 / g and the 680~850 m of ZIF-67@ZIF-8 / PAN nanofiber membranes spun in blend with PAN 2 / g, exhibiting excellent adsorption activity, it can capture gaseous SO2, NO, and NO2 small molecules by relying on van der Waals forces, trapping acidic gases in flue gas within the pores, and effectively synergistically adsorbing sulfur oxides and nitrogen oxides with efficiencies of 89.4% and 78.7%, respectively;
[0022] 2. The ZIF-67@ZIF-8 / PAN nanofiber membrane synthesized in this invention forms a porous structure, achieving a filtration efficiency of 99.9% for fine particulate matter under low pressure drop conditions;
[0023] 3. The ZIF-67 / ZIF-8 nanoparticles of the ZIF-67@ZIF-8 / PAN nanofiber membrane synthesized in this invention are grown in situ on polyacrylonitrile (PAN). Compared with the application of PAN, ZIF-67, and ZIF-8 in the preparation of nanofiber membranes, this method first prepares the nanofiber membrane and then soaks it in a coordination solution, which makes the MOFs and nanofiber membrane more firmly bonded and less prone to large-area aggregation. Compared with the traditional blending method, this method not only simplifies the synthesis process but also better preserves the original continuous network skeleton of PAN nanofibers.
[0024] 4. The Co content in the ZIF-67@ZIF-8 / PAN nanofiber membrane synthesized in this invention 2+ Zn 2+ For unsaturated coordination metal sites: O and N atoms containing a single pair of electrons in SO2, NO, and NO2 can coordinate with metal ions to form stable coordinate bonds, firmly fixing the acidic gases. The ZIF ligand is 2-methylimidazolium, and the imidazolium ring contains a large number of basic N sites (secondary amine, tertiary amine). Acidic gases SO2 and NO2 are acidic gases and will undergo acid-base protonation with the imidazolium N.
[0025] 5. The Co content in the ZIF-67@ZIF-8 / PAN nanofiber membrane synthesized in this invention 2+ It possesses oxidation catalytic activity, and under normal / medium temperature conditions, Co 2+ It can catalyze the oxidation of NO (difficult-to-adsorb nitric oxide) into higher oxidation states of nitrogen oxides such as NO2 and N2O3; the oxidized NO2 is readily captured by imidazole basic groups and metal sites, solving the problem of extremely low NO adsorption efficiency by simple physical adsorption. Zn 2+ It plays a role in stabilizing the framework and regulating porosity, preventing MOFs from agglomerating and the framework from collapsing under water vapor, and improving cycle stability. Attached Figure Description
[0026] Figure 1X-ray diffraction patterns of ZIF-67@ZIF-8 / PAN-1:3 and ZIF-67 and ZIF-8 obtained in Example 3 of the present invention are shown, wherein (a) is the X-ray diffraction pattern of ZIF-67 and ZIF-8, and (b) is the X-ray diffraction pattern of ZIF-67@ZIF-8 / PAN-1:3.
[0027] Figure 2 The images shown are scanning electron microscope (SEM) images and EDS elemental mapping images of the ZIF-67@ZIF-8 / PAN-1:3 nanofiber membrane prepared in Example 3 of this invention. (a) and (b) are SEM images of the ZIF-67@ZIF-8 / PAN-1:3 nanofiber membrane, (c) is the Co elemental mapping and its corresponding EDS image, and (d) is the Zn elemental mapping and its corresponding EDS image.
[0028] Figure 3 The above are wide-scan XPS spectra of the ZIF-67@ZIF-8 / PAN-1:3 nanofiber membrane prepared in Example 3 of this invention, wherein (a) is the full XPS spectrum of the nanofiber membrane, (b) is the high-resolution C 1s peak spectrum of the nanofiber membrane, (c) is the high-resolution O 1s peak spectrum of the nanofiber membrane, (d) is the high-resolution N 1s peak spectrum of the nanofiber membrane, (e) is the high-resolution Co 2p peak spectrum of the nanofiber membrane, and (f) is the high-resolution Zn 2p spectrum of the nanofiber membrane.
[0029] Figure 4 The Fourier transform infrared spectrum of the ZIF-67@ZIF-8 / PAN-1:3 nanofiber membrane prepared in Example 3 of the present invention.
[0030] Figure 5 The SO filter for ZIF-67@ZIF-8 / PAN prepared in Examples 1-5 of this invention x Efficiency diagram;
[0031] Figure 6 The NO filter of ZIF-67@ZIF-8 / PAN prepared in Examples 1-5 of this invention x Efficiency diagram;
[0032] Figure 7 The diagram shows the PM filtration efficiency of ZIF-67@ZIF-8 / PAN obtained in Examples 1-5 of this invention. Detailed Implementation
[0033] The above-mentioned and other technical features and advantages of the present invention will be described in more detail below with reference to the accompanying drawings.
[0034] Example 1
[0035] Preparation of ZIF-67@ZIF-8 / PAN composite material:
[0036] (1) 0.5 g of polyacrylonitrile (PAN, Mw = 150,000 g / mol) was dissolved in 7.83 g of dimethylformamide (DMF); then the solution was magnetically stirred at 40 °C for 2 hours to prepare a 6 wt% PAN polymer solution.
[0037] (2) Disperse cobalt nitrate hexahydrate (Co(Ac)2·6H2O) and anhydrous zinc nitrate (Zn(NO3)2) into PAN polymer solution, mix anhydrous zinc nitrate (Zn(NO3)2) and cobalt nitrate hexahydrate (Co(Ac)2·6H2O) in a 1:1 molar ratio, and stir at room temperature for 1 hour to obtain a uniform electrospinning solution;
[0038] (3) Pour the prepared PAN / Co(Ac)2 / Zn(NO3)2 (Zn:Co = 1:1) solution into a 10 mL syringe connected to a metal needle (size 21). Apply a 15 kV DC high voltage between the needle tip and the grounded roller. The roller is covered with silicone paper as a substrate. During the electrospinning process, the solution injection rate is set to 0.0012 mm / h, the distance from the needle tip to the roller is set to 20 cm, and the electrospinning time is set to 1.5 hours to prepare a nanofiber membrane with a ZIF-8:ZIF-67 molar ratio of 1:1, denoted as ZIF-8@ZIF-67 / PAN-1:1.
[0039] (4) Dissolve 1 g of 2-methylimidazole (2-MI) in 100 mL of ethanol to prepare a 2-MI / ethanol precursor solution. Then, immerse the nanofiber membrane spun in step (3) in the 2-MI / ethanol solution for 3 hours to perform in-situ growth of ZIF-67 / ZIF-8. Subsequently, place the nanofiber membrane in an electric heating drying oven and dry it at 60°C for 10 minutes to obtain a ZIF-67@ZIF-8 / PAN nanofiber membrane.
[0040] Example 2
[0041] The difference between this embodiment and Example 1 is that in step (2), the molar ratio of anhydrous zinc nitrate (Zn(NO3)2) and cobalt nitrate hexahydrate (Co(Ac)2·6H2O) is 1:2, resulting in a nanofiber membrane with a molar ratio of ZIF-8:ZIF-67=1:2, denoted as ZIF-8@ZIF-67 / PAN-1:2.
[0042] Example 3
[0043] The difference between this embodiment and Example 1 is that in step (2), the molar ratio of anhydrous zinc nitrate (Zn(NO3)2) and cobalt nitrate hexahydrate (Co(Ac)2·6H2O) is 1:3, resulting in a nanofiber membrane with a molar ratio of ZIF-8:ZIF-67=1:3, denoted as ZIF-8@ZIF-67 / PAN-1:3.
[0044] Example 4
[0045] The difference between this embodiment and Example 1 is that in step (2), the molar ratio of anhydrous zinc nitrate (Zn(NO3)2) and cobalt nitrate hexahydrate (Co(Ac)2·6H2O) is 1:4, resulting in a nanofiber membrane with a molar ratio of ZIF-8:ZIF-67 = 1:4, denoted as ZIF-8@ZIF-67 / PAN-1:4.
[0046] Example 5
[0047] The difference between this embodiment and Example 1 is that in step (2), the molar ratio of anhydrous zinc nitrate (Zn(NO3)2) and cobalt nitrate hexahydrate (Co(Ac)2·6H2O) is 1:5, resulting in a nanofiber membrane with a molar ratio of ZIF-8:ZIF-67=1:5, denoted as ZIF-8@ZIF-67 / PAN-1:5.
[0048] I. Characterization of ZIF-67@ZIF-8 / PAN nanofiber membrane:
[0049] 1. XRD analysis:
[0050] Figure 1 The images show X-ray diffraction patterns of ZIF-8@ZIF-67 / PAN-1:3 and ZIF-67 and ZIF-8 obtained in Example 3 of this invention. Figure 1 It can be seen that, since ZIF is a porous material similar to zeolite, Zn-based ZIF-8 and CO-based ZIF-67 have the same crystal structure. A series of sharp diffraction peaks appear at 7.4°, 10.5°, 12.8°, 14.9°, 16.5°, 18.2°, 22.2°, 24.5°, 25.6°, 26.4°, 29.5°, 31.5° and 32.4°, corresponding to the crystal planes (011), (002), (112), (022), (222), (114), (233), (002), (134), (044), (244) and (235) of ZIF-8 and ZIF-67, respectively.
[0051] 2. SEM testing:
[0052] Figure 2The images shown are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of ZIF-67@ZIF-8 / PAN-1:3 prepared in Example 3 of this invention. (a) and (b) are SEM images of ZIF-67@ZIF-8 / PAN-1:3, (c) is the Zn elemental mapping and its corresponding EDS image, and (d) is the Co elemental mapping and its corresponding EDS image. The morphology and microstructure of the synthesized MOFs and other samples were further characterized using SEM and TEM. Figure 2 The results show that after spinning, the beaded ZIF-67@ZIF-8 / PAN nanofiber membrane produces Mofs with a granular structure, such as... Figure 2 As shown in (b), a large number of irregular nanoparticles were generated and uniformly embedded in the fibrous structure. For the ZIF-67@ZIF-8 / PAN nanofiber membrane, the fibrous PAN and the particulate ZIF-67@ZIF-8 are tightly bonded together as shown in (b). Figure 2 (a). Furthermore, in the EDS elemental diagram of ZIF-67@ZIF-8 / PAN-1:3, C, N, O, Mo, Zn, In and S elements are uniformly distributed and dispersed on the filamentous PAN surface, which is consistent with the XPS results.
[0053] 3. XPS Analysis:
[0054] The surface chemical structure of the prepared ZIF-67@ZIF-8 / PAN-1:3 was analyzed using X-ray photoelectron spectroscopy (XPS). Figure 3 This further verified the chemical composition of the composite material. Figure 3 (a) shows that the ZIF-67 / ZIF-8@PAN nanofiber membrane is mainly composed of cobalt, zinc, nitrogen, oxygen, and carbon. The high-resolution spectrum of C1s has three peaks at 284.6, 286.18, and 287.6 eV, corresponding to the characteristic signals of C-C, C-N, and C-double bond O bonds, respectively. The peak of the C-N bond is generated by the coupling unit (2-Hmin). The s peak of O1 is dissociated into three peaks with binding energies of 531.24, 532.58, and 534.18 eV, respectively, attributed to CO, C-OH, and O-Co bonds. The two main peaks of N1s are the unconvolution regions of pyridine and pyrrolidone. It is worth noting that the introduction of heteroatoms (such as nitrogen and oxygen) promotes ion / electron transfer. Figure 3 (e) shows the Co core energy level spectrum, with two major peaks at 781.17 and 797.24 eV, belonging to Co2p. 3 / 2 and Co2p 1 / 2The decoupling of the Co nuclear level spectrum revealed two characteristic satellite peaks at 802.3 and 789.32 eV. In the Zn 2p nuclear level spectrum, the unconvolutional solution of Zn 2p yielded two distinct peaks with binding energies of 1021.78 and 1044.88 eV, corresponding to Zn 2p... 3 / 2 and Zn 2p 1 / 2 , can combine with Zn 2+ The oxidation states are highly matched.
[0055] 4. ATR-FITR analysis:
[0056] like Figure 4 As shown, the Fourier transform infrared spectroscopy results reveal the presence of characteristic functional groups in the material. Located at 425.06 cm⁻¹ -1 The peak at [value] represents the stretching vibration mode of C atoms in the ligands and metal center, confirming the successful formation of the framework structure. Other peaks are located at 600–1500 cm⁻¹. -1 The peak at that point represents the stretching vibration of the 2-MIm ligand. A smaller one is at 3031.34 cm⁻¹. -1 The adsorption peak at 3400 to 2200 cm⁻¹ is the result of the deprotonation process after the N–H group of the 2-MIm ligand coordinates with the metal ion; -1 The broad peak is attributed to the N–H–N bond formed between the two 2-MIm ligands. The results confirm successful MOF loading, consistent with the conclusions drawn from EDS analysis.
[0057] II. Application of ZIF-67@ZIF-8 / PAN nanofiber membranes in air filtration:
[0058] The nanofiber filter membranes prepared in Examples 1-5 were used for air filtration tests. The specific experimental procedure was as follows: the filtration performance, including filtration efficiency and pressure drop, was evaluated using a particle filtration performance test bench (XZFJ001). Potassium chloride (KCl) particles in the aerosol generator were used as model particles. The nanofiber filter membrane was placed on a metal mesh substrate with a pore size of 3 mm. Under the action of an air compressor, the airflow velocity was set to 3.0 m³ / h, and the effective filtration area was 95 cm². 2 The filtration efficiency was tested three times at each flow rate to ensure the accuracy and reliability of the experimental results. Simultaneously, the quality factor (QF) was used to comprehensively evaluate the filtration performance of the filter media. When the Co(II) to Zn(II) ratio was greater than or equal to 3:1, the air filtration efficiency reached 99.9%. Furthermore, the QF reached its highest value of 0.85 when the Co(II) to Zn(II) ratio was 3:1.
[0059] The nanofiber filter membranes prepared in Examples 1-5 were used for air filtration tests. The specific experimental procedure was as follows: the reaction temperature range was 100-300 °C, and the reaction was carried out at 110 mL / min. -1 Activity was determined in a mixed gas stream with a space velocity ratio of 16500 h⁻¹. -1 The volumetric composition of the mixed gas flow is: 0.045% NO, 0.07% NH3, 9% O2, 0.02% SO2 (when in use), and 5% H2O (when in use). N2 is used as the NO inlet and outlet of the balancing gas device. x Concentrations were measured using a MRUOPTIMA7 handheld flue gas analyzer. When the ratio of Co(II) to Zn(II) was 3:1, the effective synergistic adsorption efficiency of nitrogen dioxide and sulfur dioxide reached its highest value, at 83% and 87%, respectively.
[0060] III. Other performance tests of ZIF-67@ZIF-8 / PAN nanofiber membranes:
[0061] 1. Loop testing:
[0062] Figure 7 The figure shows the filtration performance of the ZIF-67@ZIF-8 / PAN nanofiber membrane for PM. As can be seen from the figure, the nanofiber membrane has the best filtration performance when the Co / Zn ion ratio is greater than 3:1.
[0063] 2. Nitrogen oxide filtration test:
[0064] Figure 6 The nitrogen oxide filtration tests were conducted on ZIF-67@ZIF-8 / PAN nanofiber membranes with different Co:Zn ion ratios obtained in Examples 1-5. All prepared nanofiber membranes exhibited repeatable nitrogen oxide filtration performance in the tests. The filtration efficiency of the ZIF-67@ZIF-8 / PAN nanofiber membrane was significantly higher than that of pure PAN, indicating that this composite material possesses excellent specific surface area and separation efficiency. The filtration efficiency of the ZIF-67@ZIF-8 / PAN nanofiber membrane reached its highest value when the Co:Zn ratio was 3:1. This is because ZIF-67 provides Co active sites (catalyzing denitrification and SO2 oxidation), while ZIF-8 provides a high specific surface area and microporous channels for adsorbing acidic gases; excessive Co ratios tend to aggregate and clog the pores, while excessive Zn results in insufficient catalytic activity.
[0065] 3. Sulfur oxide filtration test:
[0066] Figure 5The sulfur oxide filtration tests were conducted on ZIF-67@ZIF-8 / PAN nanofiber membranes with different Co:Zn ion ratios obtained in Examples 1-5. All prepared nanofiber membranes exhibited repeatable nitrogen oxide filtration performance in the tests. The filtration efficiency of the ZIF-67@ZIF-8 / PAN nanofiber membrane was significantly higher than that of pure PAN, indicating that this composite material possesses excellent specific surface area and separation efficiency. The filtration efficiency of the ZIF-67@ZIF-8 / PAN nanofiber membrane reached its highest value when the Co:Zn ratio was 3:1. This is because ZIF-67 provides Co active sites (catalyzing denitrification and SO2 oxidation), while ZIF-8 provides a high specific surface area and microporous channels for adsorbing acidic gases; excessive Co ratios tend to agglomerate and clog the pores, while excessive Zn results in insufficient catalytic activity.
[0067] The above description is merely a preferred embodiment of the present invention and is illustrative rather than restrictive. Those skilled in the art will understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, all of which will fall within the protection scope of the present invention.
Claims
1. A ZIF-67@ZIF-8 / PAN nanofiber membrane, characterized in that, The ZIF-67@ZIF-8 / PAN nanofiber membrane is obtained by in-situ growth of ZIF-67 / ZIF-8 nanoparticles on a polyacrylonitrile fiber matrix. The microstructure of the ZIF-67@ZIF-8 / PAN nanofiber membrane consists of smaller rhombic dodecahedral ZIF8 nanoparticles and larger rhombic dodecahedral ZIF67 nanoparticles embedded and embedded on the surface and inside of the polyacrylonitrile fiber matrix, which is formed by randomly stacked filamentous fibers.
2. A method for preparing the ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 1, characterized in that, Includes the following steps: S1, a polyacrylonitrile polymer solution is obtained by dissolving polyacrylonitrile in dimethylformamide and stirring. S2, add cobalt nitrate hexahydrate and anhydrous zinc nitrate to the polyacrylonitrile polymer solution obtained in step S1, and stir to obtain PAN / Co(Ac)2 / Zn(NO3)2 solution; S3, the PAN / Co(Ac)2 / Zn(NO3)2 solution obtained in step S2 is introduced into a syringe connected to a metal needle, and PAN / Co / Zn nanofiber membrane is obtained after electrospinning. S4. The PAN / Co / Zn nanofiber membrane obtained in step S3 is immersed in a 2-methylimidazole / ethanol precursor solution prepared by dissolving 2-methylimidazole in ethanol, and then dried to obtain ZIF-67@ZIF-8 / PAN nanofiber membrane.
3. The method for preparing a ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 2, characterized in that, In step S1, the stirring temperature is 40°C, the stirring time is 2 hours, and the concentration of the polyacrylonitrile polymer solution is 6 wt%.
4. The method for preparing a ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 2, characterized in that, In step S2, the molar ratio of cobalt nitrate hexahydrate to anhydrous zinc nitrate is 1:1 to 1:
5.
5. The method for preparing a ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 2, characterized in that, In step S2, the stirring temperature is room temperature (25°C) and the stirring time is 1 hour.
6. The method for preparing a ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 2, characterized in that, In step S3, a 15 kV DC high voltage is applied between the tip of the metal needle and the grounded roller, and the roller is covered with silicone paper as a base.
7. The method for preparing a ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 2, characterized in that, In step S3, during the electrospinning process, the solution injection rate is set to 0.0012 mm / h, the distance from the tip of the metal needle to the roller is set to 20 cm, and the electrospinning time is set to 1.5 h.
8. The method for preparing a ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 2, characterized in that, In step S3, during the electrospinning process, the temperature is controlled at 23 ± 2 ℃ and the relative humidity is controlled at 50 ± 3%.
9. A method for preparing a ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 2, characterized in that, In step S4, the PAN / Co / Zn nanofiber membrane is immersed in a 2-methylimidazole / ethanol precursor solution for 3 hours; the drying process is as follows: the membrane is dried in an electric drying oven at 60°C for 10 minutes.
10. The application of the ZIF-67@ZIF-8 / PAN nanofiber membrane as described in claim 1 in industrial flue gas denitrification and desulfurization.